UHF RFID Tag Antenna for Vehicle License Plate Number (e-Plate) - Evizal Evizal; Tharek Abdul Rahman; Sharul Kamal Abdul Rahim (Universitas Ahmad Dahlan, 2013)
In this research presents a new design of UHF RFID tag antenna for vehicle license plate number (e-plate). The proposed e-plate does not require another gadget or equipment since every vehicle is attached with a vehicle registration plate number and this e-plate embedded together. A low cost FR4 material has been used for its fabrication and there is performance improvement compared to the current tag antenna. The proposed antenna design works at 902-928 MHz frequency band for UHF RFID application with 3.8 dBi antenna gain. The antenna is rectangular in shape and has a dimension of 300 mm x 100 mm, which is usually the typical size of the conventional vehicle registration plate number. Acceptable responses were obtained in simulation at centre frequency of 915 MHz with reflection coefficient of -57.7 dB. The performance of proposed e-plate antenna was further tested by attaching a RFID tag chip and embedded it to the actual vehicle plate number. Initial testing on the field by attached e-plate on vehicle was achieved maximum reading range of up to 12 meters.